Lipopolysaccharide Binding Protein, Soluble-Intercellular Adhesion Molecule-1, Procalcitonin, and Protein C Activity and Clinical Outcome in Systemic Inflammatory Response Syndrome (SIRS) or Sepsis Patients - Dewi Muliaty; Irawan Yusuf; A Guntur Hermawan (The Indonesian Biomedical Journal, 2009)
BACKGROUND: Biochemical markers may be used in diagnosis, prognostic and monitoring treatment and therapy for sepsis patients. In this study we used Lipopolysacharide Binding Protein (LBP), serum-Intercellular Adhesion Molecule-1 (ICAM-1), Procalcitonin (PCT) and protein C activity. LBP is related to lipopolysachharide or gram-negative bacterial endotoxin which bound to LBP and induced inflammatory response. ICAM-1 is associated with endothelial dysfunction in response to systemic inflammatory and septic condition. PCT increased in bacterial infection and in severe systemic inflammatory. Role of Protein C is protecting the intravascular system to systemic inflammation, sepsis and the concomitant intravascular coagulopathy. The aim of this study was to examine the associations between levels of serum LBP, sICAM-1, PCT, and protein C activity with the clinical outcome of SIRS or sepsis patients.METHODS: We included 19 post surgery patients with SIRS criteria from intensive care unit (ICU) and evaluated the level of LBP serum with Chemiliuminescent Enzyme Immunoassay (Diagnostic Product Co.), ICAM-1 with ELISA (R&D System), PCT with immunochromatography (BRAHMS), protein C activity with chromogenic method (Dade Behring). We performed the samples serially at the first admission of patients and after 72 hours. Data were analysed by non-parametric with Wilcoxon test and Mann-Whitney test. Correlation study between biomarkers calculated by Kendall’s tau and Spearman’s rho.RESULTS: Of 19 patients, 9 (47,4%) died and 10 (52,6%) surviving. The level of LBP serum decreased after 72 hours in surviving-sepsis patients, and increased in nonsurviving sepsis patients with significant different levels at 72 hours examination (P<0.05). The level of soluble-ICAM-1 which was high in the first admission showed in non-surviving sepsis patients, but the difference levels was not significant between surviving and non-surviving patients (P>0.05). In all patients were found high level of PCT serum since the first admission examination, decreasing levels were occurred significantly in surviving patients after 72 hours (P<0.05) where high PCT levels were found in non-surviving patients after 72 hours. The median level of plasma protein C activity was low at the first admission especially in non-surviving sepsis patients, the decreasing level was not significantly different after 72 hours (P>0.05) both in surviving and non-surviving patients.CONCLUSIONS: Increasing level of LBP and PCT in sepsis patients showed that those biomarkers useful for predict the clinical outcome in sepsis patients. Decreasing protein C activity level was not a good predictor in worsening clinical outcomes. Soluble ICAM-1 level was not a good marker for predict risk of sepsis severity. LBP and PCT tests were more useful in serially testing from the first admission of sepsis patients, those tests are more faster than bacterial culture.KEYWORDS: Sepsis, SIRS, Lipopolysachharide Binding Protein, soluble- Intercellular Adhesion Molecule-1, Procalcitonin, Protein C